Variation in coagulation and fibrinolysis genes evaluated for their contribution to cerebrovascular complications in adults with bacterial meningitis in the Netherlands. Issue 1 (July 2018) - Kloek, A.T.; Khan, H.N.; Valls Seron, M.; Jongejan, A.; Zwinderman, A.H.; Baas, F.; van der Ende, A.; van de Beek, D.; Ferwerda, B.; Brouwer, M.C.
Summary: Objective: To study whether genetic variation in coagulation and fibrinolysis genes contributes to cerebrovascular complications in bacterial meningitis. Methods: We performed a nationwide prospective genetic association study in adult community-acquired bacterial meningitis patients. The exons and flanking regions of 16 candidate genes involved in coagulation and fibrinolysis pathways were sequenced. We analyzed whether genetic variation in these genes resulted in a higher risk of cerebrovascular complications, unfavorable outcome and differences in thrombocyte count on admission. Results: From 2006 to 2011, a total of 1101 bacterial meningitis patients were identified of whom 622 supplied DNA for genotyping and passed genetic quality control steps. In 139 patients (22%) the episode of bacterial meningitis was complicated by cerebral infarction, and 188 (30%) had an unfavorable outcome. We identified the functional variant rs494860 in the protein Z (PROZ) gene as our strongest association with occurrence of cerebral infarction (odds ratio (OR) 0.49 (95% confidence interval 0.33–0.73), p = 5.2 × 10 −4 ). After Bonferroni correction for multiple testing no genetic variant was significantly associated ( p -value threshold 2.7 × 10 −4 ). Conclusion: Our study suggests a functional genetic variation in the PROZ gene, rs494860, may be of importance in bacterial meningitis pathogenesis and cerebral infarction risk. Replication of this finding in other cohort studies populations is needed.